1874 Md. Laws 224 - (:unkn) unknown (My University, 1874)
An Act To Protect Wild Fowl in Worcester County, ch. 164, §§ 1-2: § 1... no person shall, during the hours intervening between twilight at evening and twilight of the following morning, shoot or kill, or shoot at, capture with nets, by fire-light, any wild fowl within the limits of Worcester County. § 2. ...no person shall, at any time, kill or shoot at any wild fowl within the limits of Worcester County, with any swivel or pivot gun, or any kind of gun which cannot be conveniently discharged from the shoulder at arms length and without a rest.
Keywords: HUNTING REGULATION